The Phenomenon of Artificial Intelligence (AI) Dependence in an Islamic Perspective on Adolescents - Didik Himmawan; Mohamad Wildan Soferino; Rindi Ariyani; Kahfiyah Rasiyani Eka Jayati (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
The use of AI technology requires regulation and ethics, as well as the responsible development of AI technology. Regulation and ethics can help ensure that AI technology is used for good purposes and does not harm society. Meanwhile, the development of responsible AI technology can help society to trust and accept AI technology. The research method used in this study is a qualitative method with a literature study approach. The research topic chosen is "The Phenomenon of Artificial Intelligence (AI) Dependence in an Islamic Perspective on Adolescents". The phenomenon of AI dependence in adolescents is a condition in which adolescents are too dependent on AI technology to carry out various daily activities such as learning, playing, communicating, and others. In facing the positive and negative impacts of AI technology, people need to understand the potential and risks of AI technology, as well as strengthen digital literacy and adaptability. Some examples of artificial intelligence-based technology devices or equipment that are widely used by teenagers today are Virtual Reality (VR), smartphones, online motorcycle taxi applications, e-commerce, google platforms, drones, and so on. Artificial Intelligence cannot fully replace the role of humans, because there is one thing that Artificial Intelligence is not able to do, which is empathy. However, Artificial Intelligence can play a role in supporting human performance. Therefore, it is necessary to develop human resource competencies, namely competencies that cannot be done by Artificial Intelligence, one of which is to improve human resource soft skills.